2017
DOI: 10.1038/tp.2016.257
|View full text |Cite
|
Sign up to set email alerts
|

Putative presynaptic dopamine dysregulation in schizophrenia is supported by molecular evidence from post-mortem human midbrain

Abstract: The dopamine hypothesis of schizophrenia posits that increased subcortical dopamine underpins psychosis. In vivo imaging studies indicate an increased presynaptic dopamine synthesis capacity in striatal terminals and cell bodies in the midbrain in schizophrenia; however, measures of the dopamine-synthesising enzyme, tyrosine hydroxylase (TH), have not identified consistent changes. We hypothesise that dopamine dysregulation in schizophrenia could result from changes in expression of dopamine synthesis enzymes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 69 publications
3
57
1
2
Order By: Relevance
“…Two PET studies have found that its levels were increased in the ventral brainstem of individuals with schizophrenia, but found no differences compared to controls in the striatum or thalamus. This is in contrast to the post‐mortem studies discussed above, but in keeping with a study showing increased VMAT2 density within platelets from individuals with schizophrenia.…”
Section: Dopaminesupporting
confidence: 48%
See 1 more Smart Citation
“…Two PET studies have found that its levels were increased in the ventral brainstem of individuals with schizophrenia, but found no differences compared to controls in the striatum or thalamus. This is in contrast to the post‐mortem studies discussed above, but in keeping with a study showing increased VMAT2 density within platelets from individuals with schizophrenia.…”
Section: Dopaminesupporting
confidence: 48%
“…Post‐mortem studies have also examined the substantia nigra. In these studies evidence regarding dopamine function is inconsistent, with some studies suggesting an increase in tyrosine hydroxylase levels in patients, but others finding no difference. Other studies have found abnormal nuclear morphology of substantia nigra neurons, reduced dopamine transporter (DAT) and vesicular monoamine transporter (VMAT) gene expression, and increased monoamine oxidase A expression.…”
Section: Dopaminementioning
confidence: 99%
“…Such an abnormal DA release produces peaks of extracellular DA, which cannot be taken up within nerve terminals, because METH inhibits and reverts the direction of the dopamine transporter (DAT). In line with this, recent studies suggest that DAT expression is significantly reduced in the midbrain of postmortem schizophrenic samples [150], which is reminiscent of the METH-addicted brain [151,152]. Upon METH administration, the massive amount of extracellular DA is followed by DA depletion, which translates into a pulsatile stimulation of post-synaptic DA receptors.…”
Section: Bridging Neurodegeneration and Psychiatric Disorders: Thementioning
confidence: 83%
“…Note the group sizes are different in the cohorts as different cases were excluded due to either poor quality RNA and/or protein. A single schizophrenia case in this mRNA cohort was lost from the mRNA cohort published previously ( 7 ) due to failure of cDNA synthesis . * p < 0.05 .…”
Section: Methodsmentioning
confidence: 90%
“…Human tissue experiments were approved by the University of New South Wales Human Research Ethics Committee (HREC #17826). Midbrain tissue was provided by the New South Wales Brain Tissue Resource Center (30/30 control/schizophrenia cases) and processed as previously described to generate mRNA and protein midbrain cohorts ( 7 ). The final midbrain mRNA cohort in this manuscript comprised 28 schizophrenia cases and 28 controls and the final midbrain protein cohort comprised 26 schizophrenia cases and 28 controls ( Table 1A ).…”
Section: Methodsmentioning
confidence: 99%